Integrated curriculum as the content of educational work in the younger grades of primary schools - Metić, Admir (Norma, 2026)
The integrated curriculum represents a modern approach in the lower grades of elementary school that overcomes traditional disciplinary fragmentation and promotes the holistic development of students of younger school age. The paper analyzes the theoretical foundations, structure and implementation of the integrated curriculum, with a focus on thematic, problematic and project models of integration. The key values of the approach are emphasized - development of personal and social identity, creativity, responsibility, cooperation, autonomy and experiential learning based on constructivist principles and Kolb’s experiential learning cycle. The importance of interdisciplinary planning, connecting areas, thematic organization of content, project-oriented activities and the role of the teacher as a facilitator is particularly emphasized. The paper considers the dynamism of planning (from learning outcomes to evaluation), indicators of success and effects on students’ motivation, critical thinking and social competence. At the same time, limitations and challenges are pointed out: rigid schedule, priority of traditional subjects, lack of resources, insufficient preparation of teachers, institutional resistance and inequalities in implementation. In conclusion, the integrated curriculum shows a significant potential for improving the quality of education in lower grades, but its effective implementation requires systemic support, continuous professional development of teachers, flexible policies and cooperation with the family and community, thus responding to the requirements of the modern European and national educational context.